Where Are We Going? Dante's Inferno or Richard Rorty's Liberal Ironist - Sansom, Dennis L. ca. 21. Jh. (Religions, 2019)
This paper elucidates the structure of moral action by arguing that Dante's explanation in the Inferno of why people end up in their respective circles of hell is superior in terms of accounting for the structure of moral reasoning to Richard Rorty's promotion of the liberal ironist. The latter suffers an internal contradictionit wants a well-lived life without any overriding aims, but such a life is understandable only in light of affirming life-aims. The former convincingly shows that the structure of action reveals the truth of the well-known apothegmwe reap what we sow. The main point for Dante is not who is rational (for even the rational can be vicious, as depicted in the Inferno), but whose aims actually fulfill the practical life. This comparison of Dante and Rorty can have larger pedagogical aims, helping students to understand better what Albert William Levi calls the moral imagination and deepening their appreciation of how metaphors and paradigms of moral excellence provide, or fail to provide, an overriding unity and purpose to our actions.